Bile acids and gestational diabetes mellitus: exploring the link and implications - a review - Lu, Chunxia; Li, Changyi; Lei, Xiaoping (Frontiers in Endocrinology, 2025)
Gestational diabetes mellitus (GDM) represents a prevalent metabolic disorder related to pregnancy, posing significant risks to both the expecting mother and the developing fetus. Recent research indicates a potential connection between bile acids (BAs) and GDM, such as lithocholic acid (LCA), β-muricholic acid (β-MCA), and 6,7-diketolithocholic acid (6,7-diketoLCA), have been found to be significantly increased in GDM individuals, thereby with the potential to reveal their involvement in glucose metabolism and the underlying mechanisms of GDM development. Additionally, BAs have emerged as vital signaling molecules that regulate glucose and lipid metabolism by interacting with Farnesoid X receptor (FXR) and Takeda G protein-coupled receptor 5 (TGR5), highlighting their potential as novel therapeutic targets for GDM management. The aim of this manuscript is to comprehensively review the current understanding of the relationship between BAs and GDM, delving into their potential mechanistic roles, diagnostic significance, and possible therapeutic applications.